Pengaruh Promosi Cashback pada OVO dan Go-Pay Terhadap Perilaku Konsumen Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Padjadjaran - Risya Nurrohyani; Estro Dariatno Sihaloho (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
In recent years, users of financial technology (fintech) have increased significantly in Indonesia due to the use of applications that are easy and fast. The most widely used financial technology (fintech) in Indonesia is OVO and Go-Pay. OVO and Go-Pay are non-cash transaction applications. The ease of use and promotions by OVO and Go-Pay are attractive for consumers. One of the promotions that are often done is cashback. Cashback is a refund from product purchases or service payments using OVO and Go-Pay. This study aims to analyze the effect of OVO and Go-Pay cashback on student’s consumption behavior of Faculty of Economics and Business in Padjadjaran University. The independent variables used are income (X_1), total using of OVO and Go-Pay (X_2), and cashback (X_3). This study used a sample of 83 students from the Faculty of Economics and Business, Padjadjaran University. The results of this study indicate income and use of OVO and Go-Pay have a positive and significant effect on student spending, while the cashback has a negative and significant effect on student spending.